2010
DOI: 10.1523/jneurosci.1223-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Coordinated Long-Term Potentiation and Dendritic Spine Enlargement at Mature Hippocampal CA1 Synapses Requires N-Cadherin

Abstract: Persistent changes in spine shape are coupled to long-lasting synaptic plasticity in hippocampus. The molecules that coordinate such persistent structural and functional plasticity are unknown. Here, we generated mice in which the cell adhesion molecule N-cadherin was conditionally ablated from postnatal, excitatory synapses in hippocampus. We applied to adult mice of either sex a combination of whole-cell recording, two-photon microscopy, and spine morphometric analysis to show that postnatal ablation of N-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 58 publications
5
129
2
Order By: Relevance
“…This model of synaptic dysfunction is also consistent with the lack of impairment in hippocampal LTP in β-cat Δex3/+ mice; enhanced cadherin stability at the synaptic membrane is unlikely to affect the insertion of additional AMPA receptors to the synaptic membrane, which is the primary mechanism responsible for LTP (34). Interestingly, basal synaptic transmission and postsynaptic strength were unaffected by the stabilization of cadherin in β-cat Δex3/+ mice, and previous studies have shown that knockdown of N-cadherin (35,36) or β-catenin (23) in vivo also did not significantly impact synapse number or basal synaptic transmission. These findings suggest that, although cadherin is important for activity-dependent plasticity, other mechanisms play a more dominant role in determining basal synapse density and synaptic strength.…”
Section: Discussionsupporting
confidence: 87%
“…This model of synaptic dysfunction is also consistent with the lack of impairment in hippocampal LTP in β-cat Δex3/+ mice; enhanced cadherin stability at the synaptic membrane is unlikely to affect the insertion of additional AMPA receptors to the synaptic membrane, which is the primary mechanism responsible for LTP (34). Interestingly, basal synaptic transmission and postsynaptic strength were unaffected by the stabilization of cadherin in β-cat Δex3/+ mice, and previous studies have shown that knockdown of N-cadherin (35,36) or β-catenin (23) in vivo also did not significantly impact synapse number or basal synaptic transmission. These findings suggest that, although cadherin is important for activity-dependent plasticity, other mechanisms play a more dominant role in determining basal synapse density and synaptic strength.…”
Section: Discussionsupporting
confidence: 87%
“…15,27,28 N-cadherin is required for critical brain processes, including long-term potentiation, pre-to post-synaptic adhesion, dendritic spine elongation -thereby regulating glutamate receptor trafficking and neuronal migration. [29][30][31][32] A bioinformatic prediction of the multiple functional associations for CDH2 is provided in Supplementary Figure 2. 33 The CDH2 N845S variant lies in the highly conserved cytoplasmic domain.…”
Section: Resultsmentioning
confidence: 99%
“…For example, N-cadherin, one of the best-characterized synaptic adhesion proteins, plays an important role in regulating dendritic spine morphology (38), basal synaptic strength, short-term plasticity, and long-term potentiation (27,(39)(40)(41)(42). Although N-cadherin interacts with a cohort of scaffolding proteins, it also binds directly to GluA2 AMPAR subunit (27,43).…”
Section: Discussionmentioning
confidence: 99%